Walking and Bicycling Suitability Assessment in Bandar Tangkak - Nur Nadia Batrisya Mohd Nazri; Umi Amirah Fauzi; Nur Imanina Syahrul Azhar; Mohd Erwan Sanik (Multidisciplinary Applied Research and Innovation, 2026)
This study investigates the walking and bicycling infrastructure in Bandar Tangkak, Johor, focusing on two neighbourhoods, namely Taman Sentosa and Taman Tangkak Jaya. As each town continues to grow in both population and traffic, evaluating the suitability of its pedestrian and cyclist facilities has become increasingly important. Using the Walking and Bicycling Suitability Assessment (WABSA) framework and Average Annual Daily Traffic (AADT) data, along with responses from a resident questionnaire. The study provides a comprehensive overview of current conditions. The findings indicate that residents tend to walk or cycle for short distance trips of less than 1.0 km. In contrast, for longer distances, they generally prefer to use private vehicles. Contributing factors include high traffic volumes, lack of continuous sidewalks, poor lighting and the absence of dedicated bicycle lanes. Many roads, especially in high-traffic areas, are either unsafe or uncomfortable for non-motorized users. The analysis points to a clear need for improvements in infrastructure to encourage more active and sustainable forms of transportation. Key recommendations include constructing safer sidewalks, developing continuous bike lanes, enhancing street lighting and improving connections between residential areas and key facilities such as schools and shops. These upgrades would not only support healthier lifestyles and reduce reliance on cars but also help create a safer and more environmentally friendly.